Guttaflow bioseal as monocone obturation technique: a scanning electron microscopy study - Mustaffa, Musliana; Nordin, Nuradlin; Embong, Siti Nur Hanie; Mohd Ibrahim, Mohamad Shafiq (Kulliyyah of Medicine, International Islamic University Malaysia, 2021)
Introduction: This study compared the obturated surface area, the extrusion of root filling material beyond the apical foramen and the duration of obturation procedure in single-rooted mandibular premolar using monocone obturation technique.